APLIKASI 3D VIRTUAL TOUR KAMPUS DENGAN TEKNOLOGI IMERSIF - Fahrul Razi; Shevti Arbekti Arman (University of Muhammadiyah Tangerang, 2026)
Digital transformation demands higher education institutions to adopt innovative and interactive promotional strategies that effectively reach prospective students. This study aims to develop a 3D Virtual Tour application using immersive technology as a campus promotion medium, implemented through the 3DVista platform. The development process follows the Multimedia Development Life Cycle (MDLC), starting from user needs identification, interface and navigation design, 360Â° panorama content documentation, to integration into an interactive application. Usability evaluation was conducted on 20 respondents using the System Usability Scale (SUS), resulting in an average score of 87.5, indicating a high level of user satisfaction. The findings demonstrate that 3D virtual tour-based promotional media not only offer an engaging digital experience but are also effective in building a modern and inclusive institutional image. This innovation is expected to serve as an adaptive, technology-based promotional alternative aligned with Asta Cita 6.